Lactoferrin perturbs intracellular trafficking, disrupts cholesterol-rich lipid rafts and inhibits glycolysis of highly metastatic cancer cells harbouring plasmalemmal V-ATPase - Pereira, Cátia Sofia Santos (2022)
Available online 16 September 2022